PERANCANGAN SISTEM INFORMASI DAN PERBAIKAN PROSES BISNIS DENGAN METODE BUSINESS PROCESS IMPROVEMENT (Studi Kasus: Koperasi Karya Mulya Situbondo) - Widiarti, Dian (Growth, 2022)
An understanding of business processes cannot be separated from understanding all production processes in an organizational unit. Harrington (1995) defines a business process as a service process that supports the production process, such as the order process (order), payment process (payrool) and manufacturing design process. So that in the business process activities are grouped using the resources owned by the organization as support in achieving organizational goals. This study aims to see an overview of the business process in the Koperasi Karya Mulya which is engaged in savings and loans activities. The absence of the use of information technology that supports business processes is the basis for this study, so that by looking at the problems that occur, recommendations can be given using the Business Process Improvement (BPI) approach. The design of the information system that is the result of this research is expected to increase the effectiveness and efficiency of existing business processes so as to improve the quality and satisfaction of the community with the services of the Koperasi Karya Mulya.